THE INFLUENCE OF SOCIAL MEDIA ADVERTISING, CUSTOMER EXPERIENCE AND RELATIONSHIP MARKETING ON CUSTOMER SATISFACTION AT JK COFFEE & ROASTERY IN BIREUEN REGENCY - Nurazizah; T. Edyansyah; Naufal Bachri; Rahmaniar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study was conducted with the aim of evaluating the extent of the influence of three main factors, namely social media advertising, customer experience, and relationship marketing on the level of consumer satisfaction at JK Coffee & Roastery located in Bireuen Regency. The researcher used a quantitative approach by applying multiple linear regression analysis techniques, and to test the hypothesis, SPSS statistical software was used as an auxiliary tool. In the sampling process, the purposive sampling method is applied, which is the selection of respondents based on special considerations or criteria that have been predetermined. The research sample consisted of 100 consumers who had made at least one to two transactions at JK Coffee & Roastery. The data collected in this study is quantitative, namely in the form of numbers used to measure variables that have been determined in the population group and sample. The main data source came from respondents who were the direct objects of this research activity. Based on the results of the analysis, it was found that the social media advertising variable (X1) showed a positive and significant influence on customer satisfaction (Y), with a significance value of 0.000 which was below the threshold of 0.05, and a tcount value of 4.435 which exceeded the ttable of 1.985, so that the first hypothesis (H1) was acceptable. On the other hand, the customer experience variable (X2) has a significance level of 0.109 over 0.05 and a tcal value of 1.613 which is still below the table, so the second hypothesis (H2) is rejected because there is no real effect on customer satisfaction. Finally, the relationship marketing variable (X3) showed a significance of 0.000 and a calculation of 5.551, both showed values that met the criteria of statistical significance, so that the third hypothesis (H3) was accepted and proved that relationship marketing plays a large and significant role in influencing customer satisfaction.